Diagnostic Imaging for Implants - Sanjay M Mallya; Anitha Potluri (Wolters Kluwer Medknow Publications, 2004)
Dental implants are a popular modality for permanent tooth replacement. The key to successful implant placement, its subsequent osseointegration and the final prosthetic rehabilitation is proper preoperative assessment. Diagnostic imaging plays an important role in the pre- and post-surgical evaluation process. Imaging is used to evaluate suitability of implant sites, aid in selection of appropriate implants, and finally evaluate implant placement and osseointegration. This article reviews the role of diagnostic imaging in the various phases and the advantages and limitations of the numerous imaging modalities.